Comparison of characteristics of women using depo-provera and intra-uterine device in a Defined Health Area - Jayasekera, C (My University, 1994)
This study revealed that the mean age of a current user of DMPA is 26.4 years whereas for an IUCD, it is 28.1 years, while the mean age at marriage was similar being 23 years, significantly more intra-uterine contraceptive device users (20.2 per cent ) compared to depo-provera users (9.5 per cent) used this method as their subsequent method after child birth; this difference is significant. Higher percentage of DMPA users (56.5 per cent) commenced using the method within first three months after childbirth compared with those using the IUCD (23.9 per cent). A little over one third of DMPA users (36 per cent) were unaware of the IUCD ( even after close questioning), whereas all users of IUCD knew their own method. This study highlights that, to increase IUCD acceptance it is important to provide regular clinic services, opportunities for women to clarify doubts by giving adequate and correct information regarding copper- T, which can be given during family planning counseling sessions. Another strategy is to direct counseling not only for potential acceptors of family planning methods as well. Another aspect is to find solutions for women who get pregnant due to IUCD failures and lastly by giving information to all women all about copper-T, which is in use at present with high effectiveness with less side effects

This study revealed that the mean age of a current user of DMPA is 26.4 years whereas for an IUCD, it is 28.1 years, while the mean age at marriage was similar being 23 years, significantly more intra-uterine contraceptive device users (20.2 per cent ) compared to depo-provera users (9.5 per cent) used this method as their subsequent method after child birth; this difference is significant. Higher percentage of DMPA users (56.5 per cent) commenced using the method within first three months after childbirth compared with those using the IUCD (23.9 per cent). A little over one third of DMPA users (36 per cent) were unaware of the IUCD ( even after close questioning), whereas all users of IUCD knew their own method. This study highlights that, to increase IUCD acceptance it is important to provide regular clinic services, opportunities for women to clarify doubts by giving adequate and correct information regarding copper- T, which can be given during family planning counseling sessions. Another strategy is to direct counseling not only for potential acceptors of family planning methods as well. Another aspect is to find solutions for women who get pregnant due to IUCD failures and lastly by giving information to all women all about copper-T, which is in use at present with high effectiveness with less side effects